Necrotizing Otitis Externa: A Proposal for Diagnostic and Therapeutic Approach - Costa, Marília Batista; Onishi, Ektor Tsuneo (International Archives of Otorhinolaryngology, 2023)
Introduction Necrotizing otitis externa has a high impact on the quality of life of patients and has shown a significant increase in its incidence in recent years. There has been a change in the profile of affected patients and a lack of consensus on the management of these patients.Objective To develop a practical and effective care protocol to standardize the diagnostic and therapeutic management of necrotizing otitis externa.Methods A retrospective cohort study of necrotizing otitis externa patients between January 2015 and December 2020.Results There were 34 patients with two bilateral cases, totaling 36 ears. The mean age was 68.5, with a higher prevalence of males (76%). Diabetes was present in 97% of the samples. The involvement of cranial pairs was identified in 35% of the sample. Pseudomonas aeruginosa was the most frequent pathogen isolated, found in 50% of the cases. Among the cultures with bacterial agents isolated, 35% showed resistance to ciprofloxacin. The most frequent exam was computed tomography (94%). Hospital admission was indicated for 31 patients (91%), and ceftazidime was the most prescribed drug (35.5%). There were 11 recurrences (32%), and 12 patients (35%) had complications during treatment. Among the unfavorable outcomes, 12% persisted with some degree of peripheral facial paralysis, 6% maintained dysphagia, and 9% died of the disease.Conclusions The present study developed a diagnostic and therapeutic protocol for the effective management of necrotizing otitis externa. This protocol is a dynamic tool and should be revised and updated as new demands emerge during its implementation.
Keywords: external otitis; skull base; osteomyelitis; diabetes mellitus; otolaryngology